PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN OCB PADA SERENE VILLAS - Putra, I Nyoman Yogi Antara; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 5 No 3 (2016), 2016)
ABSTRACT The purpose of this study was to determine the effect of transformational leadership on employee job satisfaction and organizational citizenship behavior (OCB). This research was conducted at Serene Villas Seminyak, Kuta-Bali with a sample of 94 respondents. Data were analyzed by using path analysis (path analysis). Based on the analysis, it was found that transformational leadership and significant positive effect on job satisfaction. Leaders who are able to encourage his followers to act creatively as well as leaders who are able to blend will make employees feel satisfied. Transformational leadership and significant positive effect on organizational citizenship behavior (OCB), in which the attitude of leaders who make employees comfortable work affects employees to be punctual in their work and participate in every activity. Employee satisfaction and significant positive effect on organizational citizenship behavior (OCB) in which a disgruntled employee will often talk in a positive way that will cause OCB behaviors demonstrated by helping fellow coworkers voluntarily Keywords : transformational leadership, job satisfaction, organizational citizenship behavior.
Keywords: transformational leadership, job satisfaction, organizational citizenship behavior.